Human-computer interaction for users with cerebral palsy based on head orientation. Can cursor's movement be modeled by Fitts's law?. Issue 106 (October 2017) - Velasco, Miguel A.; Clemotte, Alejandro; Raya, Rafael; Ceres, Ramón; Rocon, Eduardo
Highlights: Analysis of speed-accuracy trade-off by users with and without CP using a head mouse. Head orientation of users without motor disorders appears to follow Fitts's law. Adherence to Fitts's law is poorer for users with dystonic CP and/or ballistic movements. Users with cervical hypotonia and/or dyskinesia do not follow Fitts's law. Abstract: This paper presents an experiment to validate a head-mounted inertial interface for human-computer interaction (HCI) developed for people with cerebral palsy (CP). The method is based on Fitts's law, an empirical model of human motor performance for aimed movements. Head motion is recorded in a series of goal-crossing tasks and a regression model of the movement time ( MT ) is estimated for each user. Values of R 2 above 0.9 are indicators of a strong correlation of those motion patterns with the linear model proposed by Fitts. The analysis of MT confirmed that head movements of users without disability follow Fitts's law and showed that 3 users with CP (MACS IV and V) had the same behavior. There was a weaker correlation ( R 2 =0.839) for one individual with cervical dystonia and ballistic movements and no correlation for two users with cervical hypotonia and dyskinetic CP. Results show the impact of ballistic movements and poor postural control in computer interaction. They also provide the foundation for new interaction techniques to develop a universal computer interface for motor impaired users.